Penerapan Metode AHP dalam Penentuan Prioritas Pembangunan Jembatan Rangka di Kabupaten Deli Serdang - Marlina Br Simanjuntak; Ahmad Perwira Mulia; Gina Cynthia R. Hasibuan (Syntax Corporation Indonesia, 2023)
Bridges as an important part of the transportation system have a role in spurring economic growth and regional development. For this reason, the government is obliged to build bridge infrastructure in a stable condition so that connectivity between regions can be realized. Given the many infrastructure development activities that have been delayed since 2019 as a result refocusing as well as the limitations of the APBD, it is necessary to select the order of priority for the bridge implementation program. This study aims to analyze the dominant criteria and sub-criteria that need to be considered so that the order of priority for the construction of a truss bridge in Deli Serdang Regency can be compiled. The method used is AHP with a quantitative approach through a questionnaire. The criteria considered are economic (cost), technical (sub-criteria for bridge age, length, width, and implementation time), land use (sub-criteria for agriculture/plantation, tourism, fisheries, and mining), accessibility (sub-criteria for distance and time), social and regional development (the sub-criteria are population, social facilities, government facilities, and regional development), and policies (the sub-criteria are musrembang, Reses/Pokir DPRD, and stakeholders). The results of the study show that the dominant criteria to consider are social and regional development, followed by technical, land use, economic, policy, and accessibility criteria. The order of priority for the construction of a truss bridge is the Sei Belawan Bridge, Tanjung Anom Village as the first priority, the Bridge Lau Cirem Perpanden Village as the second priority, and Sei Serdang Bridge, Negara Beringin Village as the third priority.